Dark days on the Net. - Wallich, Paul (Wilson Quarterly)
Discusses the adverse effects of democratizing information network. Reading of messages by people other than the intended recipients; Commitment of slander by electronic impersonators; Internet's exposure to vulnerability; Provision of privacy through encryption.